SEISMIC PERFORMANCE OF RC HOLLOW RECTANGULAR BRIDGE PIERS RETROFITTED BY CONCRETE JACKETING CONSIDERING THE INITIAL LOAD AND INTERFACE SLIP - Suarjana, Made; Octora, Daniel Dixon; Riyansyah, Muhammad (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
In design practice, the assumptions that are used in retrofitting concrete structural elements often ignore the initial load and the interface slip on the contact surfaces between the old and the new concrete. The concrete structural elements that are loaded by the existing gravity load cause initial strain on the existing cross-section before jacketing is applied, while the interface does not act in a fully composite manner. In this study, a seismic performance evaluation using pushover analysis was performed of a damaged reinforced concrete bridge pier retrofitted with concrete jacketing, where the plastic hinge of the retrofitted elements was modeled by considering both parameters. The results showed that concrete jacketing could increase the capacity of the bridge structure. It was also found from the numerical result that the performance level of the bridge considering the initial load compared to the monolithic approach gave the same result since the initial load did not significantly affect the cross-sectional ultimate capacity. The difference between the ultimate capacity values computed by the two models was less than 7%. It was also shown that the interface slip had a significant effect with a slip coefficient smaller than 0.5.